IMPORTANCE OF ELECTRON MICROSCOPIC EXAMINATION IN THE DIAGNOSTICS OF ENDOMETRIAL CANCER - Safarova, S.I.; Bagirova, Sh.H.; Giblaliyeva, N.G. (World of Medicine and Biology, 2024)
Electron microscopy is crucial in diagnosing proliferative changes in endometrial cancer. Identifying atypical cells in cytology is challenging, and electron microscopy aids in overcoming this issue. This study involves patients with endometrial proliferation, including endometrial cancer, who were referred to the Oncology Clinic of AMU and observed from 1999 to 2004. Surgical samples were analyzed via light and electron microscopy. The patients were divided into three groups: highly differentiated variant (G1, n=53), moderately differentiated variant (G2, n=40), and poorly differentiated variant (G3, n=39). In highly differentiated adenocarcinomas, Findings revealed atypical glandular hyperplasia and structural deformities in desmosomes, such as reduced desmosome count in G2 tumors and complete disorganization in G3 tumors. Poorly differentiated tumors exhibited severe nuclear polymorphism, over 50 % desmosome degradation, and mitochondrial swelling, while well-differentiated adenocarcinomas showed mild nuclear deformation and less than 20 % desmosome degradation. These results offer valuable insight into the expected progression of proliferative processes in endometrial cancer, providing crucial information for understanding disease dynamics.